LAYERED INTRUSIONS AS TRANSITIONAL MAGMA CHAMBERS ABOVE THE LOCAL PLUMES OF LARGE IGNEOUS PROVINCES: EVIDENCE FROM THE EARLY PALEOPROTEROZOIC PROVINCE OF A SILICEOUS HIGHLY MAGNESIAN ROCK SERIES IN THE BALTIC SHIELD - Sharkov E.V. (My University, 2003)
It is shown, using the example of the Baltic large Early Paleoproterozoic igneous province of the siliceous, high-Mg (boninite-like) series (SHMS), that the layered intrusions had been intermediate-depth magma chambers beneath thick lava flows. Operating in these chambers had been the processes of the accumulation of periodically entered mantle-derived magmas, their crystallization differentiation, and the mixing of the fresh and evolved magmas. As a result, the magmas uprising from these chambers to the surface, are usually modified to various degrees, and primary mantle magmas are extremely rare. The origin of the SHMS magmas is believed to have been linked with large-scale assimilation of the lower-crustal material by the hot mantle-derived magmas as the new magma chamber that had originated at the crust-mantle boundary "floated'''' upward. This floating seems to have operated by the mechanism of zone refinement, that is, by way of the melting of the roof''s rocks with the simultaneous crystallization of the bottom. This "floating'''' ceased when the magma chamber reached to the essentially sialic upper crust, because a layer of light granite magma with its own convection system originated in the upper part of the chamber. Similar positions are occupied by layered intrusions in large igneous provinces (LIP) that had originated after 2 billion years ago, when a change in tectonic and magmatic activity occured. These intrusions had been formed as a result of solidification of intermediate magma chambers residing at different depths, the uppermost of which had resided immediately beneath lava plateaus and the lowermost at the crust-mantle boundary, forming up the lower continental crust from below (underplating). In all cases the LIP systems originated, irrespective of their composition, above protuberances (local plumes) on the surface of the superplumes, where the mantle material experienced melting. The character of the magma system evolution was controlled by the structure of the lithosphere, the heights of the plume rises, and the temperature of the mantle-derived magma. It is shown that the magmatic systems of the Moon highlands had been, apparently, of the same structure as those of the Earth.
Keywords: INTRUSIONS; LOCAL PLUMES; IGNEOUS PROVINCES; MAGNESIAN ROCKS; BALTIC SHIELD; MANTLE-DERIVED MAGMAS; Paleoproterozoic; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская